2019
DOI: 10.1093/geroni/igz038.2847
|View full text |Cite
|
Sign up to set email alerts
|

Access to Everyday Activities in Public Space - Views of People With Dementia

Abstract: People with dementia value staying active and continuing with their everyday lives in public space, however there is a lack of knowledge about how they experience accessibility, problematic situations and how to manage these situations. The aim is to illuminate experiences of accessibility in public space in people with dementia with focus on places, activities and problematic situations. A Grounded theory approach was used in the thesis with multiple data collection methods (interviews, focus group interviews… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 177 publications
2
12
0
Order By: Relevance
“…The ACT-OUT Questionnaire asks about the place and the journey in two discrete parts; however, according to the free text responses, the journey was described as an extension of the activity and as an opportunity to socialize with other people for various reasons (e.g., companionship, to give or to receive support). The results confirm earlier research, which identified social support as a potential strategy for managing problematic situations in public space among people with dementia [24]. Knowledge about social factors, such as social support to travel, is particularly important for participants with dementia, to facilitate a balance between capacities and limitations [2] and to enable continued social participation, following changes in their mode of participation (e.g., following driving cessation).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…The ACT-OUT Questionnaire asks about the place and the journey in two discrete parts; however, according to the free text responses, the journey was described as an extension of the activity and as an opportunity to socialize with other people for various reasons (e.g., companionship, to give or to receive support). The results confirm earlier research, which identified social support as a potential strategy for managing problematic situations in public space among people with dementia [24]. Knowledge about social factors, such as social support to travel, is particularly important for participants with dementia, to facilitate a balance between capacities and limitations [2] and to enable continued social participation, following changes in their mode of participation (e.g., following driving cessation).…”
Section: Discussionsupporting
confidence: 85%
“…Research has shown that a person's experience of public space or places outside home is linked to the type of preparatory activities that were required in the home environment. In earlier research, people with dementia reported that staying in control of participation in public space can be inhibited, and anxiety can be exacerbated because performing preparatory activities, such as finding and taking essential items including keys, a wallet, or a phone, drained their energy reserves even before departing the home environment to engage in social participation in places within public space [24]. The results suggest that greater support given to older people with and without dementia in preparatory and wayfinding stages, for example, through support using ET to help preserve energy reserves and mitigate anxiety, or the design and development of more usable wayfinding and preparatory applications within the mainstream ET that older people already use, may help to assist their ongoing social participation [15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Opportunities exist for occupational therapists in enabling participation in places and activities to support well-being as a human right (Whalley Hammell, 2017). The majority of people with dementia live in the community, which means they not only reside in their homes but also participate in a range of activities and places within public space that are cognitively demanding in various ways, for example, noise, crowding, and technology requirements (Brorsson, 2013;Winblad et al, 2016).…”
mentioning
confidence: 99%